2014
DOI: 10.1177/0013916514527590
|View full text |Cite
|
Sign up to set email alerts
|

Examining Hand-Washing Rates and Durations in Public Restrooms

Abstract: Guided by Social Learning Theory, competing hypotheses tested whether personal, environmental, or behavioral factors influenced gender differences in hand washing. A total of 170 observations were made in public restrooms on a university campus. Results suggested that differentiating patron use of urinals and commodes was appropriate for examining hand-washing differences between women and men. The research found hand-washing rates of men and women were similar if both had just used a commode. In contrast, aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…However, the medial aspect and back of the hand were the second and third most missed areas, respectively. Moreover, the interdigital area and the front and back of the fingers were the [2,3,6,[11][12][13][14]30].…”
Section: Research Implicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the medial aspect and back of the hand were the second and third most missed areas, respectively. Moreover, the interdigital area and the front and back of the fingers were the [2,3,6,[11][12][13][14]30].…”
Section: Research Implicationsmentioning
confidence: 99%
“…In contrast, Pan et al found that the number of areas of the hands that were neglected during handwashing had no correlation with the demographic data (gender, age, or profession) of participants; they also found no significant relationship between the duration of handwashing and the number of missed areas [18]. Some studies have revealed that exposure to proper hand-hygiene practices through mass media and the availability of handwashing facilities affect general handwashing practice [9,10,13].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The higher level of hygiene behaviors of females might be explained from the perspective of gender socialization theories. Cleanliness is a more important component of female gender roles because women are usually responsible for cleaning activities at home [29]. In addition, males might engage in preventive behaviors less frequently because of their greater tendency to normalize risk-taking behaviors [30].…”
Section: Hcws' Adherence To Preventive Measures and Demographic Diffe...mentioning
confidence: 99%